Thermal-induced color-changing silver plating polyamide fabrics in low electric voltage. Issue 1 (2nd January 2021) - Lu, Yawen; Xu, Lei; He, Yin; Chen, Li; Liu, Hao; Liu, Li; Li, Xiaojiu
Abstract: In this article, a simple and novel approach was presented for fabricating thermal-induced color-changing multi-layer composite fabrics (TICCF) with silver plating, polyurethane (PU) coating, and thermochromic paint pattern layer. The silver layer was plated on the polyamide fabrics by in-situ reduction of polydopamine and electroless silver plating. The results showed the surface resistivity of the polyamide fabrics with silver plating (SPPAFs) at the 50 g/L concentrations of silver nitrate is 0.0292 ± 0.0047 Ω·cm, the surface resistivity of the SPPAFs is increased to 0.1074 ± 0.0025 Ω·cm after coating with PU layer. SPPAFs/PU achieves the entire process of fading and recovery of thermochromic paint pattern during the low voltage loading and unloading process, and SPPAFs/PU shows excellent heating performance, heating sensitivity, temperature repeatability, and heating stability. TICCF will have wide application prospects in temperature alarm, smart color-changing garments, and active warm clothing fields.